Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2019)
A dataset containing 1933689 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is one of (Decaisnea insignis (Griff.) Hook.fil. & Thomson, Astelia pumila (J.R.Forst.) Gaudich., Athyrium opacum (D.Don) Copel., Hyparrhenia anemopaegma Clayton, Dendrosenecio meruensis (Cotton & Blakelock) E.B.Knox, Aegilops tauschii Coss., Diplostephium espinosae Cuatrec., Morella rubra Lour., Pteris vittata L., Phoebe omeiensis R.H.Miao, Pisum fulvum Sibth. & Sm., Diplostephium sagasteguii Cuatrec., Viscum minimum Harv., Eriocnema fulva Naudin, Soliva sessilis Ruiz & Pav., Epipactis gigantea Dougl. ex Hook., Ricotia carnosula Boiss. & Heldr., Larix potaninii var. chinensis (Beissn.) L.K.Fu & Nan Li, Rhachidosorus consimilis Ching, Gaoligongshania megalothyrsa (Hand.-Mazz.) D.Z.Li, Hsueh & N.H.Xia, Ammopiptanthus mongolicus (Maxim. ex Kom.) S.H.Cheng, Brachypodium distachyon (L.) P.Beauv., Dianthus gratianopolitanus Vill., Fritillaria pallidiflora Schrenk, Hagenia abyssinica (Bruce) J.F.Gmel., Fraxinus angustifolia Vahl, Barbarea verna (Mill.) Asch., Eurycorymbus cavaleriei (H.Lév.) Rehder & Hand.-Mazz., Stewartia cordifolia (H.L.Li) J.Li & T.L.Ming, Dolichandra cynanchoides Cham., Lonicera macranthoides Hand.-Mazz., Eriachne burkittii Jansen, Adenocalymma allamandiflorum (Bureau ex K.Schum.) L.G.Lohmann, Dracaena cambodiana Pierre ex Gagnep., Stenotaphrum secundatum (Walter) Kuntze, Alangium alpinum (C.B.Clarke) W.W.Sm. & Cave, Carpinus putoensis W.C.Cheng, Capsicum lycianthoides Bitter, Actaea vaginata (Maxim.) Compton, Alloteropsis semialata (R.Br.) Hitchc., Ilex latifolia Thunb. ex A.Murray, Salweenia bouffordiana H.Sun, Zhi M.Li & J.P.Yue, Neolamarckia cadamba (Roxb.) Bosser, Pseudolarix amabilis (J.Nelson) Rehd., Zanthoxylum simulans Hance, Homolepis aturensis (Kunth) Chase, Dendrobium huoshanense Z.Z.Tang & S.J.Cheng, Dichaetaria wightii Nees ex Steud., Sinojackia microcarpa Tao Chen & G.Y.Li, Passiflora oerstedii Mast., Flacourtia indica (Burm.fil.) Merr., Dendrotrophe varians (Blume) Miq., Magnolia grandiflora L., Lessertia frutescens (L.) Goldblatt & J.C.Manning, Fraxinus chiisanensis Nakai, Nageia nagi (Thunb.) Kuntze, Solanum umtuma Voronts. & S.Knapp, Dasypyrum villosum (L.) Borbás, Genlisea repens Benj., Fraxinus mandshurica Rupr., Tiquilia plicata (Torr.) A.T.Richardson, Cynodon dactylon (L.) Pers., Rosmarinus officinalis de Noë ex Lange, Dendrobium pendulum Roxb., Actinidia deliciosa (A.Chev.) C.F.Liang & A.R.Ferguson, Dioscorea baya De Wild., Prosphytochloa prehensilis (Nees) Schweick., Nyholmiella obtusifolia (Brid.) Holmen & E.Warncke, Ammopiptanthus nanus (Popov) S.H.Cheng, Ophioglossum californicum Prantl, Iodes cirrhosa Turcz., Fagopyrum tataricum (L.) Gaertn., Marshallia grandiflora Beadle & F.E.Boynton, Ligularia veitchiana (Hemsl.) Greenm., Diplostephium floribundum Wedd., Fatsia japonica (Thunb.) Decne. & Planch., Trifolium meduseum C.I.Blanche ex Boiss., Plantago lagopus L., Xylocarpus rumphii (Kostel.) Mabb., Phoebe sheareri (Hemsl.) Gamble, Pteridium aquilinum subsp. aquilinum, Acleisanthes obtusa (Choisy) Standl., Styrax suberifolius Hook. & Arn., Juglans cathayensis Dode, Sphagneticola trilobata (L.) Pruski, Arabidopsis halleri subsp. dacica (Heuff.) Kolník, Cajanus cajan (L.) Millsp., Chaetachme aristata Planch., Citrullus colocynthis (L.) Schrad., Paspalum juergensii Hack., Actinidia chinensis Planch., Tillandsia usneoides (L.) L., Camellia sinensis var. dehungensis (Hung T.Chang & B.H.Chen) T.L.Ming, Huperzia serrata f. longipetiolata (Spring) Ching, Alyssum desertorum Stapf, Spirogyra maxima (Hassall) Wittr., Merxmuellera tsaratananensis (A.Camus) Conert, Setaria italica (L.) P.Beauv., Dendrobium gratiosissimum Rchb.f., Camellia petelotii (Merr.) Sealy, Stewartia sinensis Rehder & E.H.Wilson, Eriochloa meyeriana (Nees) Pilg., Taxillus sutchuenensis (Lecomte) Danser, Przewalskia tangutica Maxim., Gentiana officinalis Harry Sm., Mentha spicata L., Diplostephium haenkei (DC.) Wedd., Cercis glabra Pamp., Ophrys fusca subsp. iricolor (Desf.) K.Richt., Populus lasiocarpa Oliv., Fargesia spathacea Franch., Trema orientalis (L.) Blume, Zostera marina L., Azolla filiculoides Lam., Cypripedium macranthos Sw., Strobilanthes cusia (Nees) Kuntze, Panicum virgatum L., Lavandula angustifolia Mill., Ischaemum afrum (J.F.Gmel.) Dandy, Sorghastrum nutans (L.) Nash, Cynara cardunculus var. sylvestris (Lam.) Fiori, Cicuta virosa L., Dunalia brachyacantha Miers, Merianthera pulchra Kuhlm., Solanum supinum Dunal, Paeonia ostii T.Hong & J.X.Zhang, Circaeaster agrestis Maxim., Anogramma chaerophylla (Desv.) Link, Cyrtomium falcatum (L.fil.) C.Presl, Asparagus officinalis L., Azolla caroliniana Willd., Adenocalymma biternatum (A.Samp.) L.G.Lohmann, Osmanthus marginatus (Champ. ex Benth.) Hemsl., Echinochloa oryzicola (Vasinger) Vasinger, Larix decidua Mill., Coelachne africana Pilg., Trifolium boissieri Guss., Shorea pachyphylla Ridl. ex Symington, Andropogon chrysostachyus Steud., Lathyrus clymenum L., Angiopteris evecta (G.Forst.) Hoffm., Glycine stenophita B.E.Pfeil & Tindale, Orobanche californica Cham. & Schltdl., Coccinia grandis (L.) Voigt, Lilium formosanum A.Wallace, Oryza barthii A.Chev., Chloris truncata R.Br., Vaseyochloa multinervosa (Vasey) Hitchc., Rehmannia elata N.E.Br., Diplostephium cinerascens Cuatrec., Corylus heterophylla Fisch. ex Trautv., Indocalamus wilsonii (Rendle) C.S.Chao & C.D.Chu, Schrebera orientalis Bosser & R.Rabev., Pseudosasa japonica (Siebold & Zucc. ex Steud.) Makino ex Nakai, Paeonia obovata Maxim., Illicium oligandrum Merr. & Chun, Solanum dulcamara L., Morus alba var. multicaulis (Perr.) Loudon, Pseudostellaria okamotoi Ohwi, Viola phalacrocarpa Maxim., Fragaria nipponica Makino, Gentiana crassicaulis Duthie ex Burkill, Trifolium strictum L., Lonicera ferdinandii Franch., Adenophora triphylla (Thunb.) A.DC., Libidibia coriaria (Jacq.) Schltdl., Huperzia lucidula (Michx.) Trevis., Nymphaea alba var. rubra Lönnr., Juniperus tibetica Kom., Ilex dumosa Reissek, Nymphaea mexicana Zucc., Neofinetia falcata (Thunb.) Beer, Sciadopitys verticillata (Thunb.) Siebold & Zucc., Setaria viridis (L.) P.Beauv., Biscutella lyrata L., Diphylleia grayi F.Schmidt, Carpinus cordata Blume, Parashorea macrophylla Wyatt-Sm. ex P.S.Ashton, Paeonia ×suffruticosa Andrews, Jasminum polyanthum Franch., Chlorogalum pomeridianum (DC.) Kunth, Dioscorea elephantipes (L'Hér.) Engl., Oziroe biflora (Ruiz & Pav.) Speta, Danthoniopsis dinteri (Pilg.) C.E.Hubb., Camellia yunnanensis (Pit.) Cohen-Stuart, Gentiana dahurica Fisch., Medicago hybrida (Pourr.) Trautv., Froesiochloa boutelouoides G.A.Black, Eriachne triseta Nees ex Steud., Vicia sepium L., Merrillia caloxylon (Ridl.) Swingle, Dendrosenecio brassiciformis (R.E.Fr. & T.C.E.Fr.) Mabb., Solanum macrocarpon L., Populus pseudoglauca Z.Wang & P.Y.Fu, Diplostephium cajamarquillense Cuatrec., Primulina linearifolia (W.T.Wang) Yin Z.Wang, Morus alba var. atropurpurea (Roxb.) Bureau, Genlisea filiformis A.St.-Hil., Sinopodophyllum hexandrum (Royle) T.S.Ying, Geminella minor (Nägeli) Heering, Atractylodes lancea (Thunb.) DC., Olimarabidopsis pumila (Stephan) Al-Shehbaz, O'Kane & R.A.Price, Burmannia disticha L., Melanocenchris abyssinica (R.Br. ex Fresen.) Hochst., Croomia japonica Miq., Humulus lupulus L., Diplostephium rhododendroides Hieron., Schizaea pectinata (L.) Sw., Dendrobium strongylanthum Rchb.f., Psidium guajava L., Primula chrysochlora Balf.fil. & Kingdon-Ward, Eriocaulon buergerianum Körn., Crithmum maritimum L., Glycyrrhiza lepidota Pursh, Curtisia dentata (Burm.fil.) C.A.Sm., Helianthus annuus subsp. texanus Heiser, Urochloa ruziziensis (R.Germ. & C.M.Evrard) Crins, Arabidopsis cebennensis (DC.) O'Kane & Al-Shehbaz, Sartidia perrieri (A.Camus) Bourreil, Sisymbrium irio L., Eriachne agrostidea F.Muell., Passiflora retipetala Mast., Camellia ptilophylla Hung T.Chang, Cymbidium lancifolium Hook., Cocos nucifera L., Schizaea elegans (Vahl) Sw., Juniperus formosana Hayata, Acer buergerianum subsp. ningpoense (Hance) A.E.Murray, Thalictrum thalictroides (L.) A.J.Eames & B.Boivin, Taiwania cryptomerioides Hayata, Daiswa forrestii Takht., Cannabis sativa L., Goodyera schlechtendaliana Rchb.f., Oxygraphis glacialis (Fisch. ex DC.) Bunge, Diplazium striatum (L.) C.Presl, Zelkova schneideriana Hand.-Mazz., Diplostephium cinereum Cuatrec., Schizachyrium sanguineum (Retz.) Alston, Salvia przewalskii Maxim., Podococcus barteri G.Mann & H.Wendl., Lycoris squamigera Maxim., Xanthium sibiricum Patrin ex Widder, Cinnamomum micranthum (Hayata) Hayata, Triaenophora shennongjiaensis Xiao D.Li, Y.Y.Zan & J.Q.Li, Orychophragmus violaceus (L.) O.E.Schulz, Macrosolen cochinchinensis (Lour.) Tiegh., Cinnamomum parthenoxylon (Jack) Meisn., Populus trichocarpa Torr. & A.Gray ex Hook., Lunaria rediviva L., Stewartia rubiginosa Hung T.Chang, Lilium henryi Baker, Andropogon crossotos Cope, Lilium amabile Palib., Citrullus rehmii De Winter, Bupleurum falcatum L., Schizachyrium cubense (Hack.) Nash, Ilex polyneura (Hand.-Mazz.) S.Y.Hu, Androsace paxiana R.Knuth, Artemisia selengensis Turcz. ex Besser, Coreanomecon hylomeconoides Nakai, Allium rude J.M.Xu, Hesperaloe parviflora (Torr.) J.M.Coult., Patrinia scabiosifolia Fisch. ex Trevir., Selaginella vardei H.Lév., Panicum miliaceum L., Eriachne aristidea F.Muell., Pterygopleurum neurophyllum (Maxim.) Kitag., Pharus lappulaceus Aubl., Adiantum aleuticum (Rupr.) C.A.Paris, Eriachne schultziana F.Muell., Calycanthus chinensis Cheng & S.Y.Chang, Raphidocelis subcapitata (Korshikov) Nygaard et al., Caragana kozlowii Kom., Larrea tridentata (DC.) Coville, Eulaliopsis binata (Retz.) C.E.Hubb., Ranunculus occidentalis Nutt., Lysiphyllum hookeri (F.Muell.) Pedley, Andropogon glaucescens Kunth, Dendrobium devonianum Paxton, Pheidochloa gracilis S.T.Blake, Diplostephium apiculatum S.F.Blake, Tetraphis pellucida Hedw., Leonurus japonicus Houtt., Carthamus tinctorius L., Lumnitzera racemosa Willd., Dendrobium tosaense Makino, Coix lacryma-jobi L., Chionanthus pubescens Kunth, Megacarpaea delavayi Franch., Coffea arabica L., Sphagneticola calendulacea (L.) Pruski, Lathyrus pubescens Hook. & Arn., Cephalotaxus wilsoniana Hayata, Hakonechloa macra (Munro) Honda, Magnolia odoratissima Y.W.Law & R.Z.Zhou, Fraxinus excelsior L., Itoa orientalis Hemsl., Arundinaria fargesii E.G.Camus, Zanthoxylum schinifolium Siebold & Zucc., Fagus crenata Blume)", "HasGeospatialIssue is false", "HasCoordinate is true", { "not" : { "BasisOfRecord" : [ "is Fossil" ] } } ] } The dataset includes 1933689 records from 1905 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0009881-190415153152247/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences